Parameterization and quantification of two key operando physio-chemical descriptors for water-assisted electro-catalytic organic oxidation - Bailin Tian; Fangyuan Wang; Pan Ran; Luhan Dai; Yang Lv; Yuxia Sun; Zhangyan Mu; Yamei Sun; Lingyu Tang; William A. Goddard; Mengning Ding (Nature Communications)
Abstract Electro-selective-oxidation using water as a green oxygen source demonstrates promising potential towards efficient and sustainable chemical upgrading. However, surface micro-kinetics regarding co-adsorption and reaction between organic and oxygen intermediates remain unclear. Here we systematically study the electro-oxidation of aldehydes, alcohols, and amines on Co/Ni-oxyhydroxides with multiple characterizations. Utilizing Fourier transformed alternating current voltammetry (FTacV) measurements, we show the identification and quantification of two key operando parameters (ΔI harmonics/I OER and ΔV harmonics) that can be fundamentally linked to the altered surface coverage ( $$Δ {θ }_{{{{{\rm{OH}}}}}^{*}}/{θ }_{{{{{\rm{OH}}}}}^{*}}^{{{{\rm{OER}}}}}$$ Δ θ OH * / θ OH * OER ) and the changes in adsorption energy of vital oxygenated intermediates ( $${Δ G}_{{{{\rm{OH}}}}*}^{{{{\rm{EOOR}}}}}-{Δ G}_{{{{\rm{OH}}}}*}^{{{{\rm{OER}}}}}$$ Δ G OH * EOOR − Δ G OH * OER ), under the influence of organic adsorption/oxidation. Mechanistic analysis based on these descriptors reveals distinct optimal oxyhydroxide surface states for each organics, and elucidates the critical catalyst design principles: balancing organic and M3+δ−OH* coverages and fine-tuning ΔG for key elementary steps, e.g., via precise modulation of chemical compositions, crystallinity, defects, electronic structures, and/or surface bimolecular interactions.